Rancang Bangun Sistem Wireless Sensor Salinitas Model Kapasitif - Nita Melinda; Suryono Suryono (Youngster Physics Journal, 2018)
Salinity is a significant parameter expecially to maritime aspect, such as in aquaculture and offshore agriculture. In most of measuring salinity using manual method and this is not effective. Wireless sensor of salinity using capacitive method, can be used in measuring salinity. This system consists of detector devices which is salinity sensor, processor devices which is microcontroller, and comunication devices using WiFi network. Salinity sensor is made from parallel cylinder which works by utilizing the principle of capacitance. This affect is  the frequency change of output pulse of astable multivibrator circuit. The microcontroller count the output pulse of astable multivibrator using frequency counter program. Data acquisition is made from delphi program on RTU computer. The output pulse of astable multivibrator pass the characterization process and calibration process to produce salinity value. The salinity data is stored in MySQL database and transmitted using WiFi network. The CTU computer which has been connected to the same network can access the data of salinity measurement from RTU, via a specific web address. Based on the research, the range measurement of sensor is between 2 ppt until 20 ppt, with error sensor reading is 9.11 %,. The testing of data transmission system is done by comparing the data generated from RTU and data received by CTU. The result shows that there is an error value of sending data is 0%.  Keyword: Salinity, astable multifibrator, WiFi, capacitance, web